Absolute and Relative Competence in Religious Jurisdiction in Indonesia - Khalid, Hasbuddin (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
The religious judiciary has undergone significant changes following independence. The emergence of regulations has greatly promoted progress in the field of religious judiciary in civil matters. Of particular concern is the competence of the religious judiciary, which has been renewed in line with the evolving times. In this study, we will elucidate the competence of the religious judiciary in Indonesia, taking into account the results of legislation applicable in the field of religious judiciary. The methodology in this study is a literature review, based on conceptual or normative research. Primary data in this study consist of literature studies or the examination of literature (books, journals) and research results related to the research object. The analysis used is descriptive analysis, conducted in a structured and systematic manner. The research results show that the absolute authority of the religious judiciary to examine, decide, and settle cases for the Muslim community in matters of marriage, property transfer, and Sharia economics. The material legal content in the religious judiciary has undergone numerous updates through legislation, ministerial regulations, and circulars from the supreme court. Meanwhile, the relative competence of the religious judiciary is the legal jurisdiction for the orderly functioning of the judicial system.